Qurratulain Hyder on the Move : Crossing the Frontiers of Gender, Language, and Nation - Hyder, Syed Akbar, (Middle East and Islamic Studies E-Books Online, Collection 2024., 2025)
In a career spanning seven decades, Qurratulain Hyder (1927-2007) achieved distinction as a novelist, journalist, translator, and innovator in Urdu literature. To shed new light on this multilingual itinerant woman with a curatorial eye, the present study turns to Hyder's genre-bending reportage writing, which has not yet garnered the same scholarly attention as her majestic novels and short stories. At once autobiographical, admonitory, journalistic, and lyrical, these reportages offer glimpses of Hyder's multigenerational erudition, artistry, and mastery of Perso-Urdu poetic aesthetics, as well as the challenges she faced when breaking from histories freighted by patriarchal, colonial, and nationalist enterprises.